Experimental study of the dynamics of a thin current sheet. (18th April 2016) - Gekelman, W; DeHaas, T; Van Compernolle, B; Daughton, W; Pribyl, P; Vincena, S; Hong, D
Abstract: Many plasmas in natural settings or in laboratory experiments carry currents. In magnetized plasmas the currents can be narrow field-aligned filaments as small as the electron inertial length c ω p e in the transverse dimension or fill the entire plasma column. Currents can take the form of sheets, again with the transverse dimension the narrow one. Are laminar sheets of electric current in a magnetized plasma stable? This became an important issue in the 1960s when current-carrying plasmas became key in the quest for thermonuclear fusion. The subject is still under study today. The conditions necessary for the onset for tearing are known, the key issue is that of the final state. Is there a final state? One possibility is a collection of stable tubes of current. On the other hand, is the interaction between the current filaments which are the byproduct endless, or does it go on to become chaotic? The subject of three-dimensional current systems is intriguing, rich in a variety of phenomena on multiple scale sizes and frequencies, and relevant to fusion studies, solar physics, space plasmas and astrophysical phenomena. In this study a long ( δ z = 11 m) and narrow ( δ x = 1 cm, δ y = 20 cm) current sheet is generated in a background magnetoplasma capable of supporting Alfvén waves. The current is observed to rapidly tear into a series of magnetic islands when viewed in a cross-sectional plane, but they are in essence three-dimensional flux ropes. At the onset of the current, magnetic field line reconnection is observed between the flux ropes. The sheet on the whole is kink-unstable, and after kinking exhibits large-scale, low-frequency ( f ≪ f ci ) rotation about the background field with an amplitude that grows with distance from the source of the current. Three-dimensional data of the magnetic and electric fields is acquired throughout the duration of the experiment and the parallel resistivity is derived from it. The parallel resistivity, for the most part, is not largest in the reconnection regions, but peaks in the neighborhood of large current gradients. At early times a quasi-separatrix layer (QSL) is observed where the current sheet tears, but later on a QSL of larger value, not obviously associated with reconnection, is measured at the edge of the current sheet. This QSL enhancement is connected with the rapidly spatially diverging magnetic fields in the moving sheet (ropes).